Decadal Variability of Winter Warm Arctic‐Cold Eurasia Dipole Patterns Modulated by Pacific Decadal Oscillation and Atlantic Multidecadal Oscillation. Issue 1 (24th January 2022) - Luo, Binhe; Luo, Dehai; Dai, Aiguo; Simmonds, Ian; Wu, Lixin
Abstract: In recent decades, the winter surface air temperature (SAT) anomaly in the Northern Hemisphere has exhibited a warm Arctic‐cold Eurasia (WACE) dipole pattern and this has undergone significant decadal variation. In this paper, the physical cause of the decadal variability of the WACE pattern is explored, and it is shown to be mediated by the phases of the Pacific Decadal Oscillation (PDO) and Atlantic Multidecadal Oscillation (AMO). Although the negative PDO (PDO − ) or positive AMO (AMO + ) favors the WACE pattern, the meridional structure of the pattern is significantly influenced by whether PDO − or AMO + dominates. During PDO − (AMO + ) phase, the winter‐mean WACE pattern shows an asymmetric dipole with weak (strong) warm anomaly over the Barents‐Kara Seas or BKS and strong (weak) cold anomaly over central Eurasia or Siberia, which corresponds to Ural blocking (UB) concurring with the negative (positive) phase of North Atlantic Oscillation in a winter‐mean field. The winter asymmetric WACE pattern is more strongly related to PDO − than AMO + . It is further found that an asymmetric sub‐seasonal WACE dipole pattern with strong (weak) warm anomaly over BKS and weak (strong) cold anomaly over Siberia is usually formed during the UB episode due to favored (suppressed) sub‐seasonal downward infrared radiation and turbulent heat flux over BKS during AMO + (PDO − ), which leads to a strong asymmetric dipole of the winter WACE pattern. Plain Language Summary: The most prominent climate change in the Northern Hemispheric mid‐high latitudes in recent decades is that the winter surface air temperature anomaly has exhibited a warm Arctic‐cold Eurasia (WACE) dipole pattern. However, it is still unknown what causes the decadal variability of the winter WACE pattern and its meridional asymmetry. In this paper, we address this issue by examining the different effects of Pacific Decadal Oscillation (PDO) and Atlantic Multidecadal Oscillation (AMO) on the winter WACE pattern. It is shown that PDO − (AMO + ) plays an important role in the occurrence of the asymmetric WACE dipole with weak (strong) warm anomaly over the Barents‐Kara Seas and strong (weak) cold anomaly over central Eurasia or Siberia through modulating Ural blocking and associated sub‐seasonal cold anomaly. It is also found that the asymmetric WACE dipole is more strongly dependent on PDO − than AMO + . Our findings are of great significance for understanding the physical cause of the decadal variability of the WACE dipole pattern in spatial structure. Key Points: Ural Blocking plays an important role in the occurrence of the sub‐seasonal warm Arctic‐cold Eurasia (WACE) dipole pattern in winter Ural blocking can amplify the winter‐mean Warm Arctic‐cold Eurasia (WACE) pattern Warm Arctic‐cold Eurasia (WACE) is linked to the Pacific Decadal Oscillation (PDO) and Atlantic Multidecadal Oscillation (AMO)